The Transect Method in the Study of Plant Communities in India - Puri, G. S. (Indian Forester, 1953)
The transect method in the study of plant communities is described. The methods of laying a transect, and charting quadrats are given. The ways of collecting and analysing vegetational and environmental data are described in detail and the methods of their representation and correlation with each other are enumerated with examples from author's own work. It is suggested that forest officers engaged in working plan studies may usefully employ this method for collecting data both on vegetation and its environment. The chief merits of this method are its simplicity and the great amount of information if provides at relatively less cost on the present and future condition of crop, both for exploitation and regeneration purposes. It can be usefully employed by students of vegetation throughout the country. The applicability of the method for the study of any type of vegetation is shown and the method can be used in agriculture and grassland studies as well.